When merging two international surveys (HBSC/ESPAD) leads to better monitoring at national level. (30th September 2020) - Godeau, E; Spilka, S; Ehlinger, V; Philippon, A; Lenezet, O
Abstract: In France, since 1994, adolescents' substance use was measured among 11-13-15 year-olds with the Health Behavior in School-aged Children (HBSC) & among 16-year-olds with the European School Project on Alcohol and other Drugs (ESPAD). Since 2018, with EnCLASS, (National Survey in Middle- and High-school for Adolescents on Health and Substances), France conducts those 2 surveys in a unified way across middle- & high-school, improving the monitoring of health behaviours, substance use included throughout adolescence at national level, while ensuring optimum comparability internationally. Our paper will summarise substance use by secondary students in France with a focus on preventive interventions on substances organised in class. Data collected in 2018 in 1137 classes; nationally representative sample of 20 128 secondary-school students (grade 6-12); confidential & anonymous online self-questionnaire. Schools, parents & students could refuse to participate. Inclusion rate: 74%. Secondary school is the main period where alcohol, tobacco & cannabis are experimented. With subsequent timing: Alcohol, mainly initiated during middle school, is still the first substance used during adolescence, followed by tobacco. The consumption of cannabis tends to begin at the end of middle school, with experimentation & use developing & strengthening during high school. Overall, 10% of 6th grade students report having had an intervention on substance use, up to half in 9th grade. Regarding speakers, 1/2 report external experts, 1/3 teachers & 1/4 school nurses. It seems that alcohol, tobacco & cannabis are discussed at the same occasion. Such findings show a rather good coherence between school intervention & prevalence of substance use EnCLASS by merging HBSC & ESPAD ensures an excellent comparability of data internationally while providing a strong national monitoring of French adolescents' substance use throughout secondary school.